Johana Kristofa Broces (Brotze, 1742-1823) dzīvesgājums un viņa rokrakstu kolekcija LU Akadēmiskajā bibliotēkā - Taimiņa, Aija (Latvijas Universitāte, 2013)
Promocijas darbs „Johana Kristofa Broces (Brotze, 1742-1823) dzīvesgājums un viņa rokrakstu kolekcija LU Akadēmiskajā bibliotēkā” ir interdisciplinārs humanitāro zinātņu pētījums, kas veltīts Latvijas kultūrvēsturē īpaši nozīmīgas personības biogrāfijas rekonstrukcijai un viņa darbības analīzei, un tādējādi risina bibliotēku vēstures, grāmatniecības, avotpētniecības, historiogrāfijas problēmas. Nav šaubu par to, ka pedagogs, avotpētnieks un bibliofils Broce ir viens no visspilgtākajiem Apgaismības laikmeta darbiniekiem Latvijā un Baltijā. Viņa rokrakstu un grāmatu kolekcija (kopskaitā 599 sējumi) ir kļuvusi par LU Akadēmiskās bibliotēkas dārgumu, vēsturiskās kontinuitātes apliecinājumu un bibliotēkas identitātes simbolu. Neraugoties uz to, joprojām nav tapusi Brocem veltīta monogrāfiska apcere, kas strikti balstītos uz avotu materiāliem. Pētījumam ir divi pamatvirzieni: pirmkārt, kolekcijas izveidotāja Johana Kristofa Broces dzīvesgājuma un darbības izpēte, lielākoties balstoties uz jaunapgūtiem avotiem un dokumentiem; un otrkārt, viņa kolekcijas zinātnisks izvērtējums. Broces dzīvesgājums un darbība aplūkota tā laika sociālo un sabiedrisko strāvojumu (Latvijā, Igaunijā, Krievijā, Vācijā) kontekstā. Abos aspektos pētījums aktualizē Latvijas vācbaltiešu kultūras mantojuma apguvi. Nozīmīgu vietu promocijas pētījumā ieņem ieskats Rīgas izglītības vēstures un Vidzemes guberņas ģimnāzijas (agrākā Rīgas ķeizariskā liceja) vēsturē. Visai būtisks ir ar Tartu universitāti (atjaunota 1802. gadā) kā Krievijas impērijas vācbaltiešu aprindu intelektuālo dominanti un Vidzemes guberņas skolu sistēmas pedagoģiski-administratīvo centru saistīto jautājumu loks.

The research was carried out in the Faculty of Social Sciences of the University of Latvia from 2006 to 2012. Scientific supervisor: Prof. Dr. Philol. Viesturs Zanders (University of Latvia) The research work Johann Christoph Brotze’s (1742-1823) biography and his manuscripts collection in the Academic Library of the University of Latvia is an interdisciplinary research into humanities that deals with the distinguished personality in the cultural history of Latvia, reconstruction of his biography and analysis of his activities, and thus deals with problems of library history, book publishing, research of primary sources and historiography. It is obvious that Johann Christoph Brotze, teacher, researcher of primary sources and bibliophile, is one of the most outstanding personalities of Enlightenment in Latvia and the Baltics. Brotze’s collection of manuscripts and books (altogether 599 volumes) has become the treasure, a testimony of the historical continuity and a symbol of the identity of the Academic Library of the University of Latvia. The research has two main trends: first the research of Johann Christoph Brotze’s biography and activities, based on recently acquired sources and documents; second scholarly evaluation of his collection. Brotze’s biography and activities have been investigated in the context of the respective social tendencies in Latvia, Estonia, Russia and Germany. Both the research trends make the cultural heritage of the Baltic Germans a topical issue. An overwiew of the history of Vidzeme province grammar school (former Riga King’s lyceum) and education in Riga has an important place in the research work. Issues concerning the first university in the Baltics – Tartu University (renewed in 1802) – an intellectual dominance of Baltic Germans of Russian Empire and the pedagogically- administrative centre of Vidzeme province school system have an important place in the research. The research consists of an introduction, six chapters, conclusions, list of sources and literature, supplements (11) and commentaries. The size of the work: 187 pages.
Johann Christoph Broces (Brotze, 1742-1823) and His Manuscripts Collection in the Academic Library of the University of Latvia
Keywords: Bibliotēkzinātne; Johans Kristofs Broce - biogrāfija; bibliotēku vēsture; rokrakstu kolekcijas; Latvijas historiogrāfija; avotpētniecība; Library science; Johann Christoph Brotze - Biography; manuscript collection; Latvian historiography; research of primary sources